Folic Acid-Induced Fall in Phenytoin Levels and Seizure Recurrence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Recurrence of seizures is reported in an adult after addition of folic acid for treatment of a macrocytic anemia.